Różnorodność kulturowa uczniów wyzwaniem dla współczesnej szkoły - Badowska, Mariola (Kultura-Społeczeństwo-Edukacja, 2015)
The increasing waves of migration mean that naturally comes to the interpenetration of cultures and the phenomenon of cultural diversity. Increasing real multiculturalism in Polish schools contributes to the necessity of making changes in the education system through the creation of new educational programs geared to the diversity and preparation of teaching staff, whose mission is to support and integrate culturally diverse students in the life of the school community. Effective work that allows the inclusion of students in the school environment, requires of teaching staff not only knowledge of the principles of pedagogy inclusion, but also a high level of intercultural competence, knowledge of the issues of migration, acculturation processes and the accuracy of acculturation strategies, as well as the specifics of the phenomenon of refugees and their traumatic experiences.